Pengenalan Konsep Dasar dan Praktikum Kimia Sederhana Pada Siswa Dan Guru di SMA Negeri 42 Maluku Tengah - Pada, Semuel Simra; Sutapa, I Wayan (Jurnal Gema Ngabdi, 2024)
Community service is an integral part of the Tri Dharma of Higher Education, playing a crucial role in the development of knowledge and the improvement of societal well-being. As a tangible manifestation of this responsibility, the faculty members of the Chemistry Department at FMIPA, Universitas Pattimura, conducted a community service program titled "Introduction to Basic Chemistry" at SMA Negeri 42 Maluku Tengah. This program aimed to enhance students' interest and understanding of chemistry through interactive and educational approaches. The methods employed included the dissemination of information about the Chemistry Department, the introduction of basic chemistry concepts, interactive discussions, and a survey of students' interest before and after the program. The results showed a significant increase in students' interest in chemistry, with the most substantial growth observed in their interest in further exploring and pursuing studies in the field. Positive feedback from students and accompanying teachers affirmed the effectiveness of the approach used. In conclusion, this community service program successfully achieved its primary objectives and contributed positively to strengthening scientific literacy among students. Keywords: Community service; chemistry; scientific literacy; student interest; interactive methods